An interactive planning model for sustainable urban water and energy supply. (1st February 2019) - Vakilifard, Negar; A. Bahri, Parisa; Anda, Martin; Ho, Goen
Highlights: Surplus photovoltaics output and grid electricity provide energy for water supply. Sustainable planning using a two-level mixed integer linear programming model. Short-term operational constraints are integrated with yearly planning model. Techno-economic and subjectivity criteria affect photovoltaic uptake capacity. Scenarios and sensitivity analysis are done for the case-study of Perth, Australia. Abstract: An interactive multi-period planning model is presented for sustainable urban water and energy supply, taking into account surplus output from grid-connected residential photovoltaics as a part of the water-related energy mix. The two-level mixed integer linear model finds the optimal strategic and operational decisions for a desalination-based water supply system driven by hybrid energy sources and determines the evolution of the potential capacity of a renewable energy technology over the planning horizon. It considers demands, supply systems configuration, resources capacities and electricity tariffs as well as economic, subjectivity and technical criteria for uptaking rooftop photovoltaic systems. The model was then applied to Perth (Australia) and solved for alternative scenarios. The results show operational flexibility and decentralised planning of the integrated system lead to $251, 515, 132 less discounted total cost over centralised water supply system operated in fixed mode. They also indicate that decentralised scenario results in 42, 765.1 kW higher potential photovoltaics uptake capacity on average in each year over the planning horizon in the case study area compared to centralised scenarios. However, based on the results of the sensitivity analysis, the selection of this scenario as the best alternative highly depends on the parameters values associated with subjectivity criterion and operational and maintenance cost of flexible mode of operation.